2004
DOI: 10.1007/bf02347542
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of left ventricular modification in weightlessness conditions from the spatio-temporal analysis of 2D echocardiographic images

Abstract: Two-dimensional echocardiography (2DE) performed during flights with a parabolic trajectory to simulate weightlessness provides a unique means to study left ventricular (LV) modifications to prevent post-flight orthostatic intolerance in astronauts. However, conventional analysis of 2DE is based on manual tracings and depends on experience. Accordingly, the aim was objectively to quantify, from 2DE images, the LV modifications related to different gravity levels, by applying a semi-automated level-set border d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that space flight factors could induce physiological and biochemical disorders of astronauts and lead to lots of serious health problems such as bone loss [1], cardiovascular structure and function disorder [2] and immune dysfunction [3]. To detect adverse health effects at early stage, an on-line monitoring and early alarm system for the health of astronauts must be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that space flight factors could induce physiological and biochemical disorders of astronauts and lead to lots of serious health problems such as bone loss [1], cardiovascular structure and function disorder [2] and immune dysfunction [3]. To detect adverse health effects at early stage, an on-line monitoring and early alarm system for the health of astronauts must be developed.…”
Section: Introductionmentioning
confidence: 99%